To solve the equation \( 25x^2 - 196 = 0 \) by factoring using the difference of squares pattern, we can rewrite it in a suitable form.
The equation can be recognized as a difference of squares: \[ 25x^2 - 196 = (5x)^2 - (14)^2 \] This follows the pattern \( a^2 - b^2 = (a - b)(a + b) \). Here, \( a = 5x \) and \( b = 14 \).
Using the difference of squares factoring, we have: \[ (5x - 14)(5x + 14) = 0 \]
Now, we can set each factor to zero and solve for \( x \):
-
\( 5x - 14 = 0 \) \[ 5x = 14 \implies x = \frac{14}{5} \]
-
\( 5x + 14 = 0 \) \[ 5x = -14 \implies x = -\frac{14}{5} \]
Thus, the solutions to the equation \( 25x^2 - 196 = 0 \) are: \[ x = \frac{14}{5} \quad \text{and} \quad x = -\frac{14}{5} \]
Looking at the given options, the correct response is:
- \( x = -\frac{14}{5}, ; x = \frac{14}{5} \)